2023
DOI: 10.1037/emo0001192
|View full text |Cite
|
Sign up to set email alerts
|

The representation of emotional experience from imagined scenarios.

Abstract: One of the key unresolved issues in affective science is understanding how the subjective experience of emotion is structured. Semantic space theory has shed new light on this debate by applying computational methods to high-dimensional data sets containing self-report ratings of emotional responses to visual and auditory stimuli. We extend this approach here to the emotional experience induced by imagined scenarios. Participants chose at least one emotion category label among 34 options or provided ratings on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…Although the direct connection to music might not be as apparent as in other brain areas, it is still worth further exploration. In our study, the results of the ECA module revealed the importance of high-frequency bands (beta and gamma) in distinguishing music composition states, similar to findings in emotional recognition research [ 45 , 49 , 50 ], where high-frequency bands performed slightly better than low-frequency bands (theta and alpha). This result emphasizes the close association between music and emotions, as well as the significant driving role of emotions in music composition and experience.…”
Section: Discussionsupporting
confidence: 87%
“…Although the direct connection to music might not be as apparent as in other brain areas, it is still worth further exploration. In our study, the results of the ECA module revealed the importance of high-frequency bands (beta and gamma) in distinguishing music composition states, similar to findings in emotional recognition research [ 45 , 49 , 50 ], where high-frequency bands performed slightly better than low-frequency bands (theta and alpha). This result emphasizes the close association between music and emotions, as well as the significant driving role of emotions in music composition and experience.…”
Section: Discussionsupporting
confidence: 87%
“…These stimuli have been shown to elicit discrete affective experiences that parallel the emotional space of other modalities (e.g., movies, music, facial expressions, etc.) while also facilitating more self-relevant emotional states [ 46 ]. For the present study, we selected 45 scenarios based on normative affect ratings, such that the stimulus set consisted of 15 happy, 15 neutral, and 15 sad scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…Despite substantial advances in the study of the interplay between perception and emotion, the majority of research has focused on unimodal emotional stimuli in typically developed individuals only [e.g., ( 21 , 22 )] making it challenging to discern whether and where in the brain emotional instances are represented using an abstract, rather than a sensory-dependent, code. In people with typical development, a fearful scream is likely to give rise to the mental imagery of someone in the act of screaming, and they are able to depict in their mind a specific facial expression and body posture, perhaps even a certain context, with a rich and dynamic representation close to what is commonly experienced in daily life ( 23 , 24 ). Also, this process of mental imagery is associated with a specific pattern of brain activity in relation to the different sensory channels [see, for instance, ( 25 , 26 )].…”
Section: Introductionmentioning
confidence: 99%